The Economics of Happiness Beyond Traditional Economic Growth - Rifki Suwaji; Hamy Wahjunianto; Erwin Tjahjuadi; Agus Sanjaya; Agus Iwhan Ariftian Zuhdi (PT. Anagata Sembagi Education, 2026)
Economic growth, measured by Gross Domestic Product (GDP), has long been the primary measure of a country's development success. However, recent studies have shown that increases in GDP do not always translate directly into improvements in people's subjective well-being, a phenomenon known as the Easterlin Paradox. This article aims to comprehensively examine the development of the economics of happiness as an alternative paradigm for measuring well-being beyond traditional economic growth, while simultaneously reconstructing a more holistic indicator of well-being. The method used is a narrative literature review of thirty internationally indexed scientific articles published between 2021 and 2026, analyzed using a thematic approach. The results indicate that the determinants of happiness are multidimensional, encompassing economic factors such as income, employment, and inflation; social factors such as social support, social capital, and trust; and factors such as health, freedom of choice, the environment, and sustainability. The novelty of this study lies in its integrative framework, which maps the paradigm shift from growth-centered economics to well-being-centered economics, and the proposed composite well-being index model, which is relevant for public policy formulation, including in developing countries like Indonesia. This article recommends that policymakers integrate subjective well-being indicators into national development planning so that development policies are no longer solely oriented towards growth figures, but rather towards the overall quality of life of the community